More than two intuitions: commentary - Grüning, David; Krueger, Joachim I. (Behavioral and brain sciences, 2023)
We consider an underdeveloped feature of De Neys's model. Decisions with multiple intuitions per option are neither trivial to explain nor rare. These decision scenarios are crucial for an assessment of the model's generalizability and adequacy. Besides monitoring absolute differences in intuition strength, the mind might add the strengths of intuitions per choice option, leading to competing and testable hypotheses.